Extended State Observer Based Robust Position Tracking Control Using Nonlinear Damping Gain for Quadrotors With External Disturbance - You, Sesun; Kim, Kwanyeon; Moon, Jun; Kim, Wonhee (IEEE access, 2020)
We propose an extended-state-observer (ESO)-based robust position tracking control method using nonlinear damping gain to improve the control performance under external disturbances and parameter uncertainties for quadrotors. The proposed method consists of an ESO and a nonlinear damping controller (NDC). The ESO is designed to estimate full state and disturbance. The external disturbance, velocity dynamics, and the uncertainty of the input parameter are lumped in the disturbance. The NDC is developed via backstepping procedure to suppress the output tracking error according to the disturbance estimation error. The proposed method is simple and robust against external disturbance and parameter uncertainties. In addition, only the nominal value of the input gain parameters are required. The closed-loop stability is proven by using the input-to-state stability property. The position tracking performance of proposed method was verified by performing hardware-in-the-loop simulations using a quadrotor platform.